Are Prices Countercyclical? - Prasad, Eswar (IMF Working Papers; Working Paper, 1992)
This paper examines the comovement of prices with the cyclical component of output. It argues that determining the cyclical behavior of prices by applying the same stationarity-inducing transformation to the levels of both output and prices, and examining the correlations of the resulting series, can be misleading. A more appropriate procedure is to examine the correlations between the rate of inflation and the level of the cyclical component of output. In post-war U.S. data the correlations between similarly transformed price and output data are consistently and often strongly negative, as reported recently by a number of authors as evidence of countercyclical price behavior. The rate of inflation, however, is consistently and usually strongly positively correlated with various measures of the cyclical component of output.